Peningkatan Kemampuan Literasi Keuangan & Pemasaran Produk pada UKM Fashion Konnuku.Id di Desa Palebon Semarang - Hanum, Ayu Noviani; Kristiana, Ida; Nurcahyono, Nurcahyono (STIE Pelita Nusantara, 2024)
Industry continues to experience very rapid development, thus requiring MSME players to develop products to be able to compete and compete in the industrial world. The aim of this service is to help develop one of the MSMEs in Palebon Village, Pedurungan District, Semarang City, by increasing financial literacy and product marketing skills at Konnuku.Id M&M Fashion UKM. This service is carried out on partners because partners have not carried out bookkeeping and accounting records in accordance with generally accepted accounting provisions and still have limitations in utilizing social media marketing and e-commerce as promotional and sales media, so it is necessary to provide assistance with the implementation of an accounting information system using the Zahir Accounting application. and also assistance in improving the marketing of Konnuku products through market places and also improving the quality of promotion of Konnuku.Id products on social media. The method used in this service uses the PAR (Participatory Action Research) method, namely community service oriented towards community empowerment. The result of this activity is the application of the use of Zahir accounting software to partners and maximizing social media marketing and marketplace for MSME partners so that this activity can help MSMEs develop their businesses. Keywords: financial literacy, marketing, sales